Correlates of team performance in volleyball - Drikos, S.; Kountouris, P.; Laios, A.; Laios, Y. (International Journal of Performance Analysis in Sport, 2009)
The overall performance of a Volleyball team depends on many factors, from which decisive are considered to be the execution of skills that lead immediately to winning or losing the rally. These are lost serves, aces, killattacks, attack errors and kill-blocks. The analysis of these skills in relation to team performance, as expressed by the ratio of sets won to the total number of sets, lead to the formation of two new correlates. These are the serving efficiency ratio (SER), defined as the ratio of lost serves to aces, and the attack efficiency ratio (AER), defined as the number of kill attacks divided by the sum of attack errors and kill-blocks. Analysis of the data collected from all the matches of the male A1 volleyball professional league of 2005-2006 in Greece proved that the two efficiency ratios were better predictors of the teams' overall performance than the five original variables. The findings lead to clear-cut definitions of norms both for the serving and attack efficiency ratio. The leading teams had a SER of around two and an AER of around three. These criteria are valuable tools especially for Volleyball coaches in deciding for the appropriate tactics of their teams.